PENINGKATAN MUTU SANTRI MELALUI IMPLEMENTASI INOVASI PROGRAM EKSTRAKURIKULER PESANTREN - Hilmi Qosim Mubah; Soleh , Badrus; Sufyanah, Bardatus (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2023)
Currently, there is a general view in the community that pesantren education does not only focus on being an institution for the study of Islamic knowledge, but must also be able to improve the existence of the quality of students through the development of programs outside of religion. One of these efforts is through the implementation of innovative pesantren extracurricular programs. This study aims to investigate implementation of extracurricular program innovations in improving the quality students in pesantren. This research is a literature study conducted with a qualitative approach. The sources and types of data used are secondary data in the form of scientific journals, books, skripsi and theses. There are findings that pesantren, in improving the quality their institutions, can reform through a variety extracurricular activities. Urgency improving quality students as a form of developing interests and talents, maintaining the mentality students in the pesantren and forming the identity students. The sustainability of extracurricular innovations is seen from vertical factors in the form of kyai leadership determining policies in pesantren and horizontal factors with regard to causes that intersect directly with students such as: coach strategies, support from fellow students, parents and collegiate, extracurricular SOP, availability of coaches, and support for facilities and infrastructure. Extracurricular program innovation by paying attention to the relevance of the times and the benefits obtained by students. Existence of extracurricular innovations produces graduates who are able to combine religious knowledge with general knowledge in accordance with the new times and the needs of society.